Analysis Of Non-Physical Work Environment, Work Ethics, Work Discipline On Employee Work Productivity Asn At Lldikti Region 1 North Sumatra - Nasution, Irfan Hafiz; Insan, Muhammad Yalzamul; Yanti, Eli Delvi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of the non-physical work environment, work ethics, and work discipline on the productivity of ASN (civil servant) employees at LLDIKTI Region 1 North Sumatra. The method used is quantitative with multiple linear regression analysis, involving 40 respondents determined using the Slovin formula. The results show that the three variables—non-physical work environment, work ethics, and work discipline—have a positive and significant effect on ASN productivity, both partially and simultaneously. The Adjusted R Square value of 0.413 indicates that 41.3% of the variation in employee productivity can be explained by these three variables, while the remaining 58.7% is influenced by other factors outside this study.